Strengthening the Creative Industry through Corporate Governance: The Role of Green Accounting, Intellectual Capital, Competitive Advantage, and Fintech on Financial Performance - Irwan Irwan; Wilsna Rupilu; Agusta Amanda Wulandari (Celebes Scholar pg, 2026)
This research is important and aims to provide an empirical understanding of the determining factors of the financial success of the creative industry sector in a local context, while providing strategic recommendations for business actors, local governments, and other stakeholders in encouraging the sustainability of the creative economy. The research approach used is quantitative research with explanatory research. The data used in this study are primary data in the form of questionnaires. The population in this study are creative industry actors in Kupang City spread across six Districts in Kupang City. The sampling technique uses quota sampling so that the number of samples is 60 samples. The results of the study indicate that Green Accounting, Fintech, Green Intellectual Capital, and Green Competitive Advantage have a positive and significant effect on the financial performance of the creative industry in Kupang City. In addition, Good Corporate Governance (GCG) is proven to act as a moderating variable that strengthens the relationship between the variables Green Accounting, Fintech, Green Intellectual Capital, and Green Competitive Advantage with the financial performance of the creative industry in Kupang City.